Influence of tannery wastewater sludge doses on biometric and chlorophyll fluorescence parameters in conilon coffee - Sávio Silva Berilli; Alan Alvino Falcão Zooca; Tiago Massi Ferraz; Fábio Afonso Mazei Moura de Assis Figueiredo; Weverton Pereira Rodrigues; Ana Paula Cândido Gabriel Berilli; Eliemar Campostrini (Bioscience Journal, 2018)
Tannery wastewater sludge is an industrial residue that can be used in the pure form or associated to other residues, such as byproduct production from cultivated plants. The objective of the present study was to assess substrate composition for producing conilon coffee stem cuttings, varying increasing tannery wastewater sludge doses. A randomized block design was used with four treatments, three increasing doses of tannery wastewater sludge and one conventional treatment. The stem cuttings were assessed for parameters related to photosystem II functioning and biometry. The results indicated that substrates consisting of tannery wastewater sludge, humus and subsoil promote, in general, improvement in plant growth compared to conventional substrates, highlighting the Dickson quality index. Both chlorophyll fluorescence parameters and chlorophyll contents estimates were not affected by using tannery wastewater sludge in the mixture to formulate substrate for conilon coffee stem cuttings.